2018
DOI: 10.1177/1098612x18814565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral trazodone on echocardiographic and hemodynamic variables in healthy cats

Abstract: Objectives The purpose of this study was to evaluate the effects of oral trazodone on echocardiographic variables, heart rate (HR) and blood pressure (BP) in healthy cats. Methods Client-owned domestic cats between 2 and 8 years of age were recruited. Cats were considered healthy based on physical examination, complete blood count, blood chemistry profile, urinalysis, total thyroxine concentration, non-invasive BP measurement by Doppler method and a screening transthoracic echocardiogram with simultaneous elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…Trazodone administered PO has been reported to cause excitability in horses, but in those studies, the relationship between trazodone and the observed behavioral changes also could not be clearly determined 7 . Of note, trazodone often is used in dogs and cats to minimize anxiety associated with veterinary visits and medical procedures, and the excitability seen in 1 horse in our study as well as in previous reports could represent an idiosyncratic response to the drug 12,15 …”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Trazodone administered PO has been reported to cause excitability in horses, but in those studies, the relationship between trazodone and the observed behavioral changes also could not be clearly determined 7 . Of note, trazodone often is used in dogs and cats to minimize anxiety associated with veterinary visits and medical procedures, and the excitability seen in 1 horse in our study as well as in previous reports could represent an idiosyncratic response to the drug 12,15 …”
Section: Discussioncontrasting
confidence: 64%
“…7 Of note, trazodone often is used in dogs and cats to minimize anxiety associated with veterinary visits and medical procedures, and the excitability seen in 1 horse in our study as well as in previous reports could represent an idiosyncratic response to the drug. 12,15 F I G U R E 4 Plasma trazodone and m-chlorophenylpiperazine (m-CPP) concentrations in healthy adult horses (n = 8) after multiple PO doses of trazodone hydrochloride at either 2.5 mg/kg q12 (A) or 7.5 mg/kg q12 (B).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, other sedatives cause considerable hemodynamic alterations that hinder correct interpretation of the physiologic and echocardiographic variables. [14][15][16][17][18] One study suggested that a combination of butorphanol and ketamine resulted in a significant increase in HR. Moreover, a combination of butorphanol and acepromazine leads to a significant decrease in SBP.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, if butorphanol is administered alone, it only provides light sedation, 17 which would be ineffective in overly nervous and scared cats. A recent study evaluated the effects of oral trazodone before the assessment of physiologic and echocardiographic variables, 18 and did not reveal alterations in echocardiographic rates, although SBP decreased significantly. The present study demonstrated the benefits of administering gabapentin as an anxiolytic before the assessment of physiologic and echocardiographic variables.…”
Section: Discussionmentioning
confidence: 99%
“…Trazodone hydrochloride is a serotonin antagonist/reuptake inhibitor commonly used in small animals as an adjunctive treatment for behavioral disorders and management of anxiety during hospitalization and after operative confinement 1‐4 . Trazodone is an effective sedative in cats 5,6 . Adverse effects associated with the oral administration of trazodone in small animals are generally mild.…”
Section: Introductionmentioning
confidence: 99%